Unveiling nurses’ end-of-life care experiences: Moral distress and impacts - Lee, Myung Nam (Nursing ethics, 2024)
BackgroundNurses providing care to patients with end-of-life or terminal illnesses often encounter ethically challenging situations leading to moral distress. However, existing quantitative studies have examined moral distress using instruments that address general clinical situations rather than those specific to end-of-life care. Furthermore, qualitative studies have often been limited to participants from a single unit or those experiencing moral distress-induced circumstances. A comprehensive and integrated understanding of the overarching process of moral distress is vital to discern the unique circumstances surrounding end-of-life care and its consequential impacts.Research objectivesTo explore the moral distress experiences of nurses who are frequently involved in caring for patients with end-of-life or terminal illnesses and apply it to two existing theories: the model of moral distress and the ecological model.Research designA qualitative descriptive approach was employed.Participants and research contextSeven focus group interviews involving 30 nurses were performed. The subsequent transcriptions underwent rigorous content analysis.Ethical considerationsWe obtained Institutional Review Board approval from a university. Focus group interviews were conducted with nurses who agreed to participate and signed the consent form.FindingsThe moral distress-inducing factors and nurses’ perceived impact of moral distress were identified and categorized based on moral distress theories and ecological models. A total of 15 categories and 30 subcategories across the following 4 domains were derived: (1) intrapersonal, (2) interpersonal, (3) organizational, and (4) structural factors.ConclusionsEnd-of-life-specific circumstances induced moral distress among nurses, with both negative and positive impacts identified. Effective organizational and policy support is essential to manage conflicts, form a healthy organizational culture, provide training, and prevent unnecessary expenses due to the negative consequences of moral distress.